\(\frac{1}{10}\)+ \(\frac{4}{20}\)+ \(\frac{9}{30}\)+ \(\frac{16}{40}\)+ \(\frac{25}{50}\)+ \(\frac{36}{60}\)+ \(\frac{49}{70}\)+ \(\frac{64}{80}\)+ \(\frac{81}{90}\)
= \(\frac{1}{10}\)+ \(\frac{2}{10}\)+ \(\frac{3}{10}\)+ \(\frac{4}{10}\)+ \(\frac{5}{10}\)+ \(\frac{6}{10}\)+ \(\frac{7}{10}\)+ \(\frac{8}{10}\)+ \(\frac{9}{10}\)
= ( \(\frac{1}{10}\)+ \(\frac{9}{10}\)) + ( \(\frac{2}{10}\)+ \(\frac{8}{10}\)) + ( \(\frac{3}{10}\)+ \(\frac{7}{10}\)) + ( \(\frac{4}{10}\)+ \(\frac{6}{10}\)) + \(\frac{5}{10}\)
= \(1+1+1+1\) + \(\frac{5}{10}\)
= \(4+\frac{5}{10}\)
= \(\frac{40}{10}\)+ \(\frac{5}{10}\)
= \(\frac{45}{10}\)
= \(\frac{9}{2}\)
Vậy kết quả sau khi rút gọn là \(\frac{9}{2}\)nhé!